2015
DOI: 10.5194/jsss-4-31-2015
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent determination of nitrite traces in water solutions using cellulose as sorbent

Abstract: Morphology and photoluminescence (PL) properties for microcrystalline cellulose (MCC), microcrystalline nitrite powders of common formulae MNO 2 (M = Na, K) (MCN) and two-component materials composed of both MCC and MCN have been prepared and characterized by means of optical microscopy and luminescence spectroscopy. This study aimed to clarify a possibility of low-limit determination of the nitrite traces in water solutions by luminescent method.Published by Copernicus Publications on behalf of the AMA Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…The described data are similar to ones earlier reported by us for the microcrystalline cellulose samples and some other "cellulose-oxide" composites [12,13,16]. Besides, mentioned characteristics are similar to those published elsewhere concerning luminescence of various cellulosebased materials [5,[8][9][10].…”
Section: Luminescent Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…The described data are similar to ones earlier reported by us for the microcrystalline cellulose samples and some other "cellulose-oxide" composites [12,13,16]. Besides, mentioned characteristics are similar to those published elsewhere concerning luminescence of various cellulosebased materials [5,[8][9][10].…”
Section: Luminescent Propertiessupporting
confidence: 79%
“…At the same time, they are of interest as materials for applications in electronic and opto-electronic devices, e.g. such as solar cells, supercapacitors, lithium-ion batteries, flexible "paper" electronics [5][6][7] and luminescent materials [8][9][10] particularly for their potential applications as chemical and biological sensors or for toxic chemical removing [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We denote the composites of such type here as W-NaNO 2 and W-CsNO 3 . The details both of the oxides synthesis and the samples preparation can be found in [36,37,44,48,49].…”
Section: Methodsmentioning
confidence: 99%
“…Those were scanning electron microscopy (SEM), chemical elements analysis, X-ray diffractometry (XRD), luminescence spectroscopy and dielectric characteristics measurements. Equipment and any other details of experimental study can be found also in [36,37,44,48,49].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation